INVESTIGATING STUDENTS’ PERCEPTIONS OF USING FLIPPED CLASSROOM IN EFL WRITING - Nabila Mudzakarah; Adila Putri; Muhammad Rizky Fauzan; Naf’an Tarihoran (INJOSEDU: International Journal of Social and Education, 2026)
This study aims to investigate students’ perceptions of the implementation of the flipped classroom method in EFL writing. A quantitative approach with a descriptive survey design was used in this study. The participants were 50 students from the English Education Study Program at UIN Sultan Maulana Hasanuddin Banten. Data were collected through a questionnaire distributed via Google Forms and analyzed using descriptive statistics. The results show that students generally have positive perceptions of the flipped classroom. The method helps students better understand writing materials, improves their writing skills, and increases their readiness before class through pre-learning activities. In addition, students become more active and engaged during classroom activities, and the level of interaction also improves. Furthermore, the flipped classroom enhances students’ confidence and motivation in writing. Students also find the method easy to follow and feel comfortable using it. Most of them prefer the flipped classroom over traditional learning methods. The flipped classroom is an effective approach for teaching EFL writing, as it supports students’ learning experiences and promotes a more interactive and student-centered learning environment